The Contribution of Metal Mining to Southeast Sulawesi’s Economy: An Input-Output Analysis - Manzilia Fatma; Amy Yayuk Sri Rahayu (Journal Research of Social Science, Economics, and Management, 2025)
Abstrak. The metal mining sector, particularly nickel mining in Southeast Sulawesi, Indonesia, plays a crucial role in regional economic growth but faces challenges in achieving sustainable development. Despite contributing significantly to the Gross Regional Domestic Product (GRDP), the sector exhibits relatively low economic multipliers and weak integration with upstream and downstream industries. This study aims to analyze the economic impact of the metal mining sector by quantifying its multiplier effects and sectoral linkages using an Input-Output model. Employing the 2023 Input-Output Table for Southeast Sulawesi and applying Leontief multiplier analysis, the research evaluates income, employment, and surplus multipliers as well as backward and forward linkages within 52 economic sectors. The results reveal that while the sector’s contribution to GRDP increased by 40.63% from 2019 to 2023, its multiplier effects remain limited compared to secondary and tertiary sectors. Simulation shows that increasing nickel production could raise regional GRDP by 3% but has minimal national impact. The findings underscore the necessity of strengthening downstream processing, enhancing sectoral linkages, and pursuing economic diversification to maximize benefits and ensure long-term regional economic resilience. This study provides valuable insights for policymakers aiming to foster sustainable development in resource-rich regions.